Thermal energy confinement time of spherical tokamak plasmas in PI3 - A. Tancetti; C. Ribeiro; S.J. Howard; S. Coop; C.P. McNally; M. Reynolds; P. Kholodov; F. Braglia; R. Zindler; C. Macdonald; E. Love; P. Carle; et al. (Nuclear Fusion)
The Plasma Injector 3 (PI3) experiment at general fusion has been constructed to demonstrate the ability to form plasma targets suitable for compression in a Magnetized Target Fusion machine. To achieve compressive heating to fusion conditions, the target plasmas should have an energy confinement time sufficiently in excess of the compression time. In this work we present a methodology for calculating this timescale and present results for a large set of discharges. Characterization of the plasma current profiles reveals trends and groupings determined by machine settings. The largest energy confinement times have been obtained for discharges with a broad plasma current profile, fresh lithium coating on the device walls, and a near constant toroidal field. We find that PI3 plasmas at $5\,ms$ into the discharge can have thermal confinement times in excess of $10\,ms$ . These meter-scale plasma can thus achieve significant heating if compressed on a timescale of milliseconds.